Karakteristik Budaya Organisasi: Sebuah Studi Kualitatif terhadap Pengusaha Batik Muslim Laweyan Surakarta - Lukman Hakim; Irwan Abdullah; Nurus Sa'adah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2021)
This study aims to identify (1) the cultural characteristics of the Muslim batik entrepreneurs in the Batik Industry in Surakarta. (2) the values that underlie the cultural organization of Muslim batik entrepreneurs in the Laweyan Batik Industry, Surakarta. The research locations were Mahkota Batik, Putra Laweyan Batik, Gres Tenan Batik, Puspa Kencana Batik and Merak Manis Batik. This type of research uses descriptive-qualitative methods. The results of the study conclude the cultural characteristics of Muslim batik entrepreneurs organizations, as follows: (1) culture of struggle (al Mujahadah), (2) culture of togetherness (al Ijtimaiyyah), (3) culture of mutual help (at Tawauniyyah), (4) culture of humanity (al Insanniyyah), (5) professional culture (al Ihtirofiyyah), (6) creative and innovative culture (al kholaq wal mubtakar), (7) thoroughness culture (as shihah), and (8) skill culture (al khibrah).